On‐coil multiple channel transmit system based on class‐D amplification and pre‐amplification with current amplitude feedback. Issue 1 (13th August 2012) - Gudino, Natalia; Heilman, Jeremiah A.; Riffe, Matthew J.; Heid, Oliver; Vester, Markus; Griswold, Mark A.
Abstract A complete high‐efficiency transmit amplifier unit designed to be implemented in on‐coil transmit arrays is presented. High power capability, low power dissipation, scalability, and cost minimization were some of the requirements imposed to the design. The system is composed of a current mode class‐D amplifier output stage and a voltage mode class‐D preamplification stage. The amplitude information of the radio frequency pulse was added through a customized step‐down DC‐DC converter with current amplitude feedback that connects to the current mode class‐D stage. Benchtop measurements and imaging experiments were carried out to analyze system performance. Direct control of B1 was possible and its load sensitivity was reduced to less than 10% variation from unloaded to full loaded condition. When using the amplifiers in an array configuration, isolation above 20 dB was achieved between neighboring coils by the amplifier decoupling method. High output current operation of the transmitter was proved on the benchtop through output power measurements and in a 1.5T scanner through flip angle quantification. Finally, single and multiple channel excitations with the new hardware were demonstrated by receiving signal with the body coil of the scanner. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.